English question formation: a comparison of errors made by English-Dominant versus Mandarin-Dominant learners in a Chinese medium primary school - Wong, Ai Li; Ayeshah Syed, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Students from different language backgrounds may face distinct difficulties when learning English, particularly in learning complex language structures such as questions. Therefore, identifying differences between learner groups can inform teaching practice. This paper presents the findings from a study on the production of English questions by 56 Year 4 national-type Chinese primary school students, categorised as Dominant Speakers of English (n=28) or Dominant Speakers of Mandarin (n=28). The objectives of the study were 1) to identify common errors in English questions produced by the students in a translation task and 2) to compare the errors made by Mandarin-dominant and English-dominant learners. The researchers obtained data via written language elicitation tasks, to examine the kinds of errors made by the learners. Data was analysed using an adapted version of Rowland’s error analysis framework. Comparison of data from a 10-item translation task showed that Mandarin-dominant learners made more than twice the errors of English-dominant learners. Common errors across both groups were auxiliary tenses errors and omission errors in WH-questions and auxiliary errors in Yes/No questions. Furthermore, Mandarin-dominant learners made visibly more auxiliary, omission, and position-of-question-word errorsthan English-dominant learners, while the latter had a higher proportion of double-marking errors. This study provides further evidence that learners from different backgrounds may face different challenges in acquiring features of English. Moreover, the findings could provide insights for English language teachers in Chinese-medium schools on how to better adapt the teaching of English questions to their students of different language backgrounds.